European evidence-based guidelines on pancreatic cystic neoplasms - Del Chiaro, Marco; Hackert, Thilo (Gut, 2018)
Evidence-based guidelines on the management of pancreatic cystic neoplasms (PCN) are lacking. This guideline is a joint initiative of the European Study Group on Cystic Tumours of the Pancreas, United European Gastroenterology, European Pancreatic Club, European-African Hepato-Pancreato-Biliary Association, European Digestive Surgery, and the European Society of Gastrointestinal Endoscopy. It replaces the 2013 European consensus statement guidelines on PCN. European and non-European experts performed systematic reviews and used GRADE methodology to answer relevant clinical questions on nine topics (biomarkers, radiology, endoscopy, intraductal papillary mucinous neoplasm (IPMN), mucinous cystic neoplasm (MCN), serous cystic neoplasm, rare cysts, (neo)adjuvant treatment, and pathology). Recommendations include conservative management, relative and absolute indications for surgery. A conservative approach is recommended for asymptomatic MCN and IPMN measuring <40 mm without an enhancing nodule. Relative indications for surgery in IPMN include a main pancreatic duct (MPD) diameter between 5 and 9.9 mm or a cyst diameter ≥40 mm. Absolute indications for surgery in IPMN, due to the high-risk of malignant transformation, include jaundice, an enhancing mural nodule >5 mm, and MPD diameter >10 mm. Lifelong follow-up of IPMN is recommended in patients who are fit for surgery. The European evidence-based guidelines on PCN aim to improve the diagnosis and management of PCN.
Collaborators: Marco Del Chiaro, Marc G. Besselink, Marco J. Bruno, Djuna L. Cahen, Thomas M. Gress, Jeanin E. van Hoof, Markus M. Lerch, Julia Mayerle, Lianne Scholten, Thilo Hackert, Alessandro Zerbi, David Cunningham, Claudio Gi De Angelis, Enrique de-Madaria, Peter Hegyi, Jonas Rosendahl, Helmut Friess, Riccardo Manfredi, Philippe Lévy, Francisco X. Real, Alain Sauvanet, Mohammed A. Hilal, Giovanni Marchegiani, Irene Esposito, Paula Ghaneh, Marc R.W. Engelbrecht, Paul Fockens, Nadine C.M. van Huijgevoort, Christopher Wolfgang, Claudio Bassi, Natalya B. Gubergrits, Caroline Verbeke, Günter Klöppel, Aldo Scarpa, Giuseppe Zamboni, Anne Marie O'Broin-Lennon, Malin Sund, Nikolaos Kartalis, Lars Grenacher, Urban Arnelo, Kostantin V. Kopchak, Kofi Oppong, Colin McKay, Truls Hauge, Kevin Conlon, Mustapha Adham, Güralp O. Ceyhan, Roberto Salvia, Christos Dervenis, Peter Allen, François Paye, Detlef K. Bartsch, Matthias Löhr, Massimiliano Mutignani, Johanna Laukkarinen, Richard Schulick, Roberto Valente, Thomas Seufferlein, Gabriele Capurso, Ajith Siriwardena, John P. Neoptolemos, Aldis Pukitis, Ralf Segersvärd
Gesehen am 09.12.2020